RAGAM KOMUNIKASI DALAM AL-QUR’AN - Fitri Yanti, Fitri Yanti (BINA' AL-UMMAH, 2017)
The verses of the Qur'an can be grouped into several forms of communication. The Qur'an is a concrete example of how God always communicates with His servants through revelation. In addition, the Prophet SAW also communicate with family, friends and ummah.The study of communication that is integrated with the Qur'anic verses with various scientific dimensions of the Qur'an provides answers to problems that are often experienced by one of them by explaining some variety of communication in various contexts of conversation. As long as humans live in society, so long as the communication also plays an important role. The Qur'an refers to communication as one of human nature. In the analysis of the verses of the Qur'an that contain communication problems. As a book, the Qur'an contains various forms of communication. When viewed from the eyes of Islamic scholarship, the Qur'an contains good news (basyiran) and warning (nadhiran). However, when viewed from the science of communication verses of the Qur'an can be grouped into several forms of communication, including, interpersonal, interpersonal, intercultural, group communication, mass communication, etc. Although the Qur'an does not specifically address the problem of communication but there are images of ways of communicating.